Cromolyn sodium reduces LPS-induced pulmonary fibrosis by inhibiting the EMT process enhanced by MC-derived IL-13 - Cheng Tan; Hang Zhou; Qiangfei Xiong; Xian Xian; Qiyuan Liu; Zexin Zhang; Jingjing Xu; Hao Yao (Respiratory Research)
Abstract Background Sepsis is a systemic inflammatory response caused by infection. When this inflammatory response spreads to the lungs, it can lead to acute lung injury (ALI) or more severe acute respiratory distress syndrome (ARDS). Pulmonary fibrosis is a potential complication of these conditions, and the early occurrence of pulmonary fibrosis is associated with a higher mortality rate. The underlying mechanism of ARDS-related pulmonary fibrosis remains unclear. Methods To evaluate the role of mast cell in sepsis-induced pulmonary fibrosis and elucidate its molecular mechanism. We investigated the level of mast cell and epithelial-mesenchymal transition(EMT) in LPS-induced mouse model and cellular model. We also explored the influence of cromolyn sodium and mast cell knockout on pulmonary fibrosis. Additionally, we explored the effect of MC-derived IL-13 on the EMT and illustrated the relationship between mast cell and pulmonary fibrosis. Results Mast cell was up-regulated in the lung tissues of the pulmonary fibrotic mouse model compared to control groups. Cromolyn sodium and mast cell knockout decreased the expression of EMT-related protein and IL-13, alleviated the symptoms of pulmonary fibrosis in vivo and in vitro. The PI3K/AKT/mTOR signaling was activated in fibrotic lung tissue, whereas Cromolyn sodium and mast cell knockout inhibited this pathway. Conclusion The expression level of mast cell is increased in fibrotic lungs. Cromolyn sodium intervention and mast cell knockout alleviate the symptoms of pulmonary fibrosis probably via the PI3K/AKT/mTOR signaling pathway. Therefore, mast cell inhibition is a potential therapeutic target for sepsis-induced pulmonary fibrosis.